Analysis of Nutritional Status of Junior High School 3 Belawa Wajo Regency - Iyan, Iyan; Usman, Usman (International Journal of Technology and Education Research, 2025)
This study aims to obtain answers to the research question: What is the nutritional status of students at Junior High School 3 Belawa Wajo, Regency. This research is descriptive in nature with a single (independent) variable. The study population consisted of 81 female students of Junior high School 3 Belawa Wajo, class IX, in 2024. The research sample comprised 30 students selected through purposive sampling. The data analysis technique used was descriptive analysis (percentage) employing the SPSS Version 18.00 software. Based on the results of data analysis, it can be concluded that the nutritional status of the female students in class IX Junior High school 3 Belawa Wajo in 2024 varied according to the following classification: Low = 14 students (48%), Ideal = 14 students (45.33%), and Overweight = 2 students (6.67%). The mean value was 17.4317, with a standard deviation of 2.,6521 variance of 8.765, range of 12.16, minimum value of 13, 78, and maximum value of 24.72. Therefore, it can be concluded that the nutritional status of the female students in class IX at Junior High School 3 belawa , Wajo in 2024 was predominantly in the Low Body category.